Health and Growth : Commission on Growth and Development - Spence, Michael; Lewis, Maureen (World Bank, 2012)
The commission on growth and development was established in April 2006. It felt that the benefits of growth were not fully appreciated, but also recognized that the causes of growth were not fully understood. Growth is often overlooked and underrated as an instrument for tackling the world's most pressing problems, such as poverty, illiteracy, income inequality, unemployment, and pollution. At the same time, grasp of the sources of growth in developing countries is less definitive than commonly thought even though advice is sometimes given to policy makers in these countries with great confidence, perhaps greater than the state of knowledge will justify. Consequently, the commission's mandate is to 'take stock of the state of theoretical and empirical knowledge on economic growth with a view to drawing implications for policy for the current and next generation of policy makers. Good health improves the capacity to learn and work, which dramatically improves income and welfare at the household level even if the effects at the aggregate level may be harder to discern. The methodological problems in capturing these gains deserve attention and further work. More attention also needs to be paid to upgrading healthcare institutions, as more of the same is neither affordable nor desirable.